Treatment satisfaction and its association with anxiety, depression and fear of COVID-19 among Lebanese inpatients with schizophrenia. - BITAR, Zeinab; HADDAD, Chadia; OBEID, Sahar; HALLIT, Souheil (Pharmacy Practice (1886-3655))
Background: The patient's evaluation of treatment and its associated outcomes define the treatment satisfaction. The quality of treatment satisfaction and healthcare service has been affected by depression, anxiety and fear of the current coronavirus disease 2019 (COVID-19) pandemic. Objective: Therefore, this study aimed to assess factors associated with treatment satisfaction among Lebanese inpatients with schizophrenia, namely depression, anxiety and fear of COVID-19. Methods: A cross-sectional study was conducted between September and November 2020, enrolled 118 patients with chronic schizophrenia consecutively admitted to Psychiatric Hospital of the Cross, Lebanon. The Functional Assessment of Chronic Illness Therapy-Treatment Satisfaction-Patient Satisfaction Scale (FACIT-TS-PS) was used to assess treatment satisfaction, the Lebanese Anxiety Scale -10 (LAS-10) was used to assess anxiety, Montgomery-Asberg Depression Rating Scale (MADRS) to assess depression and the Fear of COVID-19 Scale to assess the level of fear of the COVID-19 pandemic. Results: The mean scores of the scales were as follows: treatment satisfaction (65.20; SD 16.11; median=71), LAS-10 (13.65; SD 6.02), MADRS (9.09; SD 6.69) and fear of COVID-19 (18.59; SD 6.78). Higher depression (r= -0.46, p<0.001) was significantly associated with lower treatment satisfaction. Female gender (beta=7.51, p=0.029) was significantly associated with higher treatment satisfaction score. Fear of COVID-19 did not show any significant association with the treatment satisfaction score. Conclusions: Results of this study found that depression and gender were associated with treatment satisfaction among inpatients with schizophrenia. No association has been found between fear of COVID-19 and treatment satisfaction among those patients. More research is warranted to evaluate treatment satisfaction and associated factors among chronic inpatients with schizophrenia, specifically during the COVID-19 pandemic, in order to improve treatment satisfaction and subjective well-being of patients.